Guarding minds: a narrative review on how n-acetylcyteine and ketones could shield sensitive patients from antibiotic neurotoxicity - Lounici, Astrid (Frontiers in Pharmacology, 2025)
BackgroundAntibiotics, indispensable in combating infectious diseases and extending life expectancy, are among the most commonly prescribed medications globally. However, neurotoxicity, encompassing neurological and psychiatric adverse effects, is an underrecognized phenomenon associated with all major classes of antibiotics. Certain antibiotics, such as fluoroquinolones, carry risks of permanent damage, including central and peripheral nervous system injury and mitochondrial dysfunction. Sensitive populations, such as the elderly and individuals with compromised organ function or genetic predispositions, are particularly vulnerable.AimsTo review evidence on the neurological and psychiatric side effects of antibiotics and evaluate potential neuroprotective strategies like N-acetylcysteine (NAC) and ketone bodies.MethodNarrative review of preclinical and clinical studies, clnical case reports and epidemiological data.ResultsNeurological and psychiatric side effects are rare, but they can be devastating. NAC shows promise in preclinical studies for mitigating oxidative stress and cellular damage. Ketones, through ketogenic diets or exogenous supplementation, may provide neuroprotection via enhanced mitochondrial function and anti-oxidative and anti-inflammatory effects.ConclusionWhile initial findings are promising, further research is required to validate the clinical efficacy of these protective agents. Improved understanding of antibiotic neurotoxicity and potential mitigation strategies could lead to safer prescribing practices, particularly for vulnerable populations, balancing risk mitigation with the essential benefits of antibiotics.